THE DESIGN OF A MODEL FOR THE INTELLECTUAL CAPITAL MEASUREMENTIN MANUFACTURING COMPANIES IN PERU - García Zapata, Teonila (2005)
The Model for the intellectual capital measurement in a manufacturing company in Peru has an important value for being the key element to know the structure of the intangible assets of the company and its capability to generate value. The creation of value does not depend on physical assets only, but increasingly on intangible assets. That is why the indicators of the intellectual capital are being identified and built, so that the model guarantees, that the results to be obtained are acceptable and credible.